Moses revisited. August Strindberg’s and Edvard Munch’s dramatic use of the figure of Moses (Altre Modernità, 2011)
In this essay I explore the literary interpretation of the figure of Moses in August Strindberg’s and Edvard Munch’s contemporary plays, Genom öknar till arvland (Through Deserts to Ancestral Lands, 1903) and Den fri Kjærligheds By (The City of Free Love, ca. 1905). In the first case, the focus is on the examination of Moses as an archetypical character. Analogies are subsequently drawn between the biblical hero and other dramatic characters in the production of the Swedish playwright, such as Gustav Vasa or Birger jarl. In the latter case, I outline the strategy for a parodic reuse of the biblical source in Munch’s invention of a modern Moses created to mock his fellow painter and maestro Christian Krohg and the bohemian ideal of free love. Although the qualities of the Moses character take on different and opposite meanings in the two authors, it is of interest that the issue of a return to the common heritage of biblical culture should make itself evident in the years following both Strindberg’s and Munch’s farewell to the secular milieus of the Bohème.